The relationship between obsessive–compulsive symptoms and depressive symptoms in patients with obsessive–compulsive disorder: A network analysis - Zhujing Ma; Lei Ren; Li Guo; Fengzhan Li; Yinchuan Jin; Wei Liang; Qintao Zhang; Huiling Yuan; Qun Yang (Indian Journal of Psychiatry)
Aim: The network model suggests that the comorbidity of obsessive–compulsive disorder (OCD) and depression is due to direct interactions between OCD and depression symptoms. The study investigates the network structure of OCD and depressive symptoms in patients with OCD and explores the pathways that connect the OCD and depression symptoms. Materials and Methods: The items of Yale-Brown Obsessive–Compulsive Symptom (Y-BOCS) Scale and the Depression Self-Rating Scale of 445 patients with OCD were analyzed by network model. Statistical analysis and visualization of the network were conducted using R software. Results: Two bridge edges “uneasiness” and “time consumed by obsessions” and “low spirit” and “distress caused by obsessions” connected the OCD symptoms to depressive symptoms. Two closely related edges were between “interference due to obsessions” and “interference due to compulsions” and between “difficulty resisting obsessions” and “difficulty resisting compulsions.” The symptoms “interference due to compulsions,” “distress caused by obsessions,” “time consumed by compulsions,” and “uneasiness” had the highest expected influence centrality. Conclusions: This study highlighted the relationship between “uneasiness” and “time consumed by obsessions” and between “low spirit” and “distress caused by obsessions.” In addition, “interference due to compulsions” is found as the core symptom in the network. Targeting these symptoms may help prevent and treat the comorbidity of obsession–compulsion and depression in patients with OCD.